El movimiento de olimpiadas de matemática en secundaria: un reto para Costa Rica (ING) - Adolio, Norma (2003)
This article describes the Costa Rica Mathematics Olympiads for Secondary School, which for a long time has and great success in this country and has contributed to the improvement of mathematics in this school level. This project gives us important resources for competition in relevant annual international tournaments and a-llows us to participate with other counties in this kind of competitions which measure the mathema-tical reasoning of teenagers with special abilities for mathematical problem solving.